World Economic Outlook, April 2014 : Recovery Strengthens, Remains Uneven. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2014)
The world economy continues its slow recovery from the global financial crisis, but the main impetus for growth now lies with the advanced economies. The April 2014 WEO examines the causes and implications of recent trends, including increased financial volatility in emerging market economies, lower-than-expected inflation in advanced economies, and the withdrawal of monetary accommodation. It examines the policy priorities for both advanced economies and emerging market developing economies. The report includes a chapter that analyzes the causes of worldwide decreases in real interest rates since the 1980s and another chapter that examines factors behind the fluctuations in emerging market economies' growth, including the role of China.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet